Effect of sudden expansion for varied area ratios at subsonic and sonic flow regimes - Sethuraman, Vigneshvaran; Thong, Kenny Tan Boon; Khan, Sher Afghan (Trinity College of Engineering and Research, Pune, 2016)
This study investigates the effect of sudden expansion of air for varied area ratio and length-to-diameter ratio of pipes, at subsonic and sonic flow regimes. It was found that the flow reattaches at approximately same location of the pipe, irrespective of the area ratio for the cases 2.56 and 3.61. At minimal area ratio of 1.69, the flow does not reattach due to insufficient area for the flow to expand.